The microcystic, elongated and fragmented (MELF) pattern of invasion: a single institution report of 464 consecutive FIGO grade 1 endometrial endometrioid adenocarcinomas - Joehlin-Price, Amy S. (Am J Surg Pathol, 2017)
MELF invasion has been associated with non-vaginal recurrences and lymph node (LN) metastases in multi-institutional case control studies, but has not been well examined in large single institution cohorts. Hysterectomy specimens with FIGO 1 endometrioid endometrial carcinoma (EEC) and lymphadenectomies from 2007 to 2012 were identified. Electronic medical records and histologic slides were reviewed. Of 464 identified cases, 163 (35.1%) were noninvasive, 60 (12.9%) had MELF, 222 (47.8%) had a component of the infiltrative invasion pattern without MELF, 13 (2.8%) had pure pushing borders of invasion, 5 (1.1%) had pure adenomyosis-like invasion, and 1 (0.2%) had pure adenoma malignum-like invasion. Sixteen cases had LN metastases. Significantly more MELF cases had positive LNs than non-MELF cases overall (18.3% vs 1.2%, p<0.001). The results were almost identical when invasive infiltrative cases with and without MELF were compared (18.3% vs 1.8%, p<0.001). The maximum number of MELF glands per slide did not differ between cases with and without LN metastases, p=0.137. A majority of positive LNs, even in MELF cases, demonstrated non-histiocyte-like metastases. Only five cases (all with MELF invasion) demonstrated micrometastatic lesions or isolated tumor cells only. MELF cases demonstrated a non-significant decrease in time to extra-vaginal recurrence (p=0.082, log-rank test), for which analysis was limited by low recurrence rates. In summary, MELF is associated with LN metastases, even when compared to other infiltrative cases, and shows multiple patterns of growth in positive LNs. MELF cases additionally trended toward decreased time to extra-vaginal recurrence.